Pemenuhan Restitusi Dan Kompensasi Sebagai Bentuk Perlindungan Bagi Korban Kejahatan Seksual Dalam Sistem Hukum Di Indonesia - Atikah Rahmi (DE LEGA LATA: JURNAL ILMU HUKUM, 2019)
Sexual crime is a form of crime that harasses and tarnishes human dignity. These crimes have a tremendous impact on victims, in the form of physical, psychological, economic and social. The impact experienced by victims will actually increase with the reaction of the community when women become victims. The condition of the victims was increasingly cornered, they became limited in carrying out their social roles. Victims experience prolonged trauma that requires recovery. Legal protection efforts against women and children victims of sexual crimes are a struggle for their rights. Restitution and compensation are forms of protection as an integral part of human rights in the field of welfare and social security, a form of protection that must be met for victims of sexual crimes. The concept of compensation for victims so far still relies on the concept of restitution charged directly to the perpetrators. This paradigm should have been changed, especially for victims of sexual crimes, both child and adult. Victims of sexual crime should no longer rely on the obligations of the perpetrators, but also the responsibility of the State by providing compensation to victims.